UMP makes tech leaps with society in mind - T. N., Alagesh (2022)
UNIVERSITI Malaysia Pahang (UMP) has implemented environmentally friendly initiatives to make its campus sustainable in line with the country's Sustainable Malaysia 2030 aspiration.